A glimpse of freedom: Allied occupation and political resistance in East Germany - Luis R. Martínez; Jonas Jessen; Guo Xu (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
This paper studies costly political resistance in a non-democracy. When Nazi Germany surrendered in May 1945, 40% of the designated Soviet occupation zone was initially captured by the western Allied Expeditionary Force. This occupation was short-lived: Soviet forces took over after less than two months and installed an authoritarian regime in what became the German Democratic Republic (GDR). We exploit the idiosyncratic line of contact separating Allied and Soviet troops within the GDR to show that areas briefly under Allied occupation had higher incidence of protests during the only major episode of political unrest in the GDR before its demise in 1989 - the East German Uprising of 1953. These areas also exhibited lower regime support during the last free elections in 1946. We argue that even a "glimpse of freedom" can foster civilian opposition to dictatorship.
Keywords: F51; H10; N44; P20; 330; East Germany; political resistance; protest; autocracy; spatial RDD; World War II